First Canadian Reports of Cervical Adenitis due to Mycobacterium malmoense and a 10-Year Review of Nontuberculous Mycobacterial Adenitis. Issue 2 (1st April 2006) - McCrossin, Chris; Mailman, Tim
Abstract : The present report reviews a decade of experience with nontuberculous mycobacterial adenitis at a pediatric referral centre, noting that patients are often subjected to multiple ineffective antibiotic courses, and that delays in diagnosis and referral for appropriate therapy are common. Notable clinical features include a mean age of presentation of 3.4 years, a male-to-female ratio of 1:1.5 and a gradual onset of painless, unilateral cervical adenopathy. Fever was absent in most patients (77%), and the disease failed to respond to antistaphylococcal antibiotics. The mean time to correct diagnosis was longer than three months (15 weeks). The clinical features of the disease are highlighted and presented with a practical diagnostic approach to the child with subacute/chronic adenitis. New molecular diagnostic tools and emerging mycobacteria are discussed, including the first reports of Mycobacterium malmoense adenitis in Canada.